Review: Effect of Milking Frequency on Milk Quantity and Quality in Ewes - Habibi, Emal (Journal of Natural Sciences – Kabul University, 2023)
Milking frequency is one of the main factors regulating milk quantity and quality. The Reduction of daily milking frequency in dairy Sheep farms is a good strategy to reduce milk prices and improve farmers' lives. To reduce the number of workers and milking time, different milking frequency can be used such as eliminating milking once or twice a week, milking once a day, milking three times in two days. The effect of milking frequency on milk quantity and quality varies in different breeds. In general, reducing the frequency of milking reduces the quantity of milk, significant savings in labor and time spent in the milking parlour, but increasing the frequency of milking, increases the quantity of milk and reduces the quality of milk. In this article, the effect of milking frequency on milk quantity and quality in ewes has been reviewed.